Adapted agency: how connected (Dutch) police professionals rework their professional capabilities. Issue 2 (10th March 2022) - Meurs, Teun; Noordegraaf, Mirko
Abstract: Increasingly, public professionals deal with complex issues, stakeholders, and publics. The so-called protective notions of professionalism no longer seem sufficient; they are reconfigured into more 'connective' forms. This involves dealing with tensions, dilemmas, and contradictions, calling for abilities to tackle these. Professionals will have to work on how they work, on their standards, routines, and practices. On the basis of an action-oriented research project, aimed at understanding the rise and results of new forms of police professionalism, we analyze what Dutch police professionals actually do when they perform connective work. We focus on policing, as this field experiences a transition from practice-based to knowledge-intensive forms of professionalism, relating police actions to societal stakeholders and issues. Based on observations of work practices of higher educated police professionals as well as interviews and educational interventions, we conclude that police professionals cannot simply 'apply' knowledge and competencies to practice, in order to solve societal problems. Rather, they gradually 'develop' capabilities (i.e., situational, analytical, and normative capabilities), in order to combine different forms of professional knowledge in real-life situations. Our research shows this is complicated. They 'mess with' how police professionalism 'normally' works. Police professionals are adapting their agency; they are performing 'agency work'. They try to get a sense of the situation, explore multiple viewpoints, and demonstrate their added value. We argue that our conclusions are relevant for other professional fields.